SYMPTOMATIC FEATURES OF INTRAPLATE EARTHQUAKES - Gangopadhyay A.; Talwani P. (My University, 2003)
Available geological, geophysical, and seismological data for 39 cases were compared and analyzed to understand the cause of intraplate earthquakes. The results revealed common features which can be used to test models for their seismogenesis. Intraplate seismicity occurs in the vicinity of "stress concentrators" within pre-existing zones of weakness, most commonly failed rifts. These stress concentrators are structures where plate tectonic stresses can cause a localized buildup of stresses and, ultimately, earthquakes. These include intersecting faults, buried plutons, and rift pillows. One of the intersecting faults was often found to be tens of kilometers in length and oriented optimally with respect to the maximum horizontal stress direction. Intraplate earthquakes have longer return periods compared to their plate-boundary counterparts. They occur in failed rifts of all ages, whereas those not associated with rifts occur only in the Precambrian crust. The former have shorter return periods (< 500 years) compared to the latter (thousands of years).